Analisis Kesalahan Berbahasa Dalam Wacana Media Sosial Lawan Covid-19 - Apri Dani Yanti; Khairunnisa Hatminingsih; Sintia Pratiwi (PIKTORIAL : Journal of Humanities, 2020)
This study aims to analyze language errors on the CoV Opposite social media page 19. Analysis of language errors is a method or step used by researchers to identify, collect data, errors, explain errors, classify errors and evaluate the seriousness of language errors. The data taken is sourced from Instagram and Twitter lawancovid19_id. This study uses the method of collecting recorded data collection techniques, the follow-up technique is the note taking technique. Based on the results of the analysis that has been done, it can be concluded that writing on social media is against Covid 19. On Instagram and twitter lawancovid19_id there are some language errors including the use of foreign terms, the use of punctuation, the use of slang, the use of conjunctions and the use of writing. Keyword: Language error, social media, Covid-19